Nϵ-Carboxymethyl-Lysine Deteriorates Vascular Calcification in Diabetic Atherosclerosis Induced by Vascular Smooth Muscle Cell-Derived Foam Cells - Xu, Sui-Ning; Zhou, Xin; Zhu, Cun-Jun; Qin, Wei; Zhu, Jie; Zhang, Ke-Lin; Li, Hui-Jin; Xing, Lu; Lian, Kun; Li, Cheng-Xiang; Sun, Zhen; Wang, Zhong-Qun; et al. (Frontiers in Pharmacology, 2020)
Nε-carboxymethyl-lysine (CML), an advanced glycation end product, is involved in vascular calcification (VC) in diabetic atherosclerosis. This study aimed to investigate the effects of CML on VC in diabetic atherosclerosis induced by vascular smooth muscle cell (VSMC)-derived foam cells. Human studies, animal studies and cell studies were performed. The human study results from 100 patients revealed a poor blood glucose and lipid status and more severe coronary lesions and stenosis in patients with coronary artery disease and diabetes mellitus. Intraperitoneal injection of streptozotocin combined with a high-fat diet was used to build a diabetic atherosclerosis model in ApoE−/− mice. The animal study results indicated that CML accelerated VC progression in diabetic atherosclerosis by accelerating the accumulation of VSMC-derived foam cells in ApoE−/− mice. The cell study results illustrated that CML induced VSMC-derived foam cells apoptosis and aggravated foam cells calcification. Consistent with this finding, calcium content and the expression levels of alkaline phosphatase, bone morphogenetic protein 2 and runt-related transcription factor 2 were significantly elevated in A7r5 cells treated with oxidation-low-density lipoprotein and CML. Thus, we concluded that CML promoted VSMC-derived foam cells calcification to aggravate VC in diabetic atherosclerosis, providing evidence for the contribution of foam cells to diabetic VC.